Bactericidal Activities of Two Daptomycin Regimens against Clinical Strains of Glycopeptide Intermediate-Resistant Staphylococcus aureus, Vancomycin-Resistant Enterococcus faecium, and Methicillin-Resistant Staphylococcus aureus Isolates in an In Vitro Pharmacodynamic Model with Simulated Endocardial Vegetations - Akins, Ronda L. (American Society for Microbiology, 2001)
Daptomycin is an investigational lipopeptide antibiotic active against gram-positive organisms. The mechanism of action is unique, resulting in interference with cell membrane transport. The bactericidal activity of daptomycin was evaluated against glycopeptide-intermediate susceptible Staphylococcus aureus (GISA), vancomycin-resistant Enterococcus faecium (VREF), and methicillin-resistant S. aureus (MRSA) in an in vitro infection model with simulated endocardial vegetations. Simulated regimens of daptomycin at 6 mg/kg/day (D6) and 10 mg/kg/day (D10) were utilized. MICs and MBCs for daptomycin were determined in the absence and in the presence of albumin with the following results (MIC/MBC): for GISA-992, 0.5/1.0 and 16/16; for VREF-590, 2.0/2.0 and 32/32; and for MRSA-494, 0.25/0.25 and 1.0/4.0 μg/ml, respectively. During the first 8 h daptomycin significantly reduced the inoculum for all organisms. Daptomycin at 6 mg/kg/day and 10 mg/kg/day had log(10) CFU/g reductions of 5 and 6, 3.4 and 5, and 6.4 and 6.5 by 8 h for GISA-992, VREF-590, and MRSA-494, respectively. Against both GISA-992 and VREF-590, the D10 regimen achieved the limit of detection at 72 h, with D6 regimens showing slight regrowth. A concentration-dependent killing effect was noted to occur, with daptomycin demonstrating a more rapid and greater kill from the D10 versus the D6 regimen. The results of this study suggest that daptomycin demonstrates significant (P < 0.05) activity against gram-positive organisms in a simulated sequestered infection site.